2017
DOI: 10.5888/pcd14.160606
|View full text |Cite
|
Sign up to set email alerts
|

Daily Sugar-Sweetened Beverage Consumption, by Disability Status, Among Adults in 23 States and the District of Columbia

Abstract: IntroductionInformation on dietary intake, including sugar-sweetened beverages (SSBs), for adults with disabilities is limited. Such information can inform interventions to prevent chronic disease and promote health among adults with disabilities. The objective of this study was to describe the associations between SSB consumption and disability among adults.MethodsWe examined data on adults aged 18 years or older in 23 states and the District of Columbia who participated in the 2013 Behavioral Risk Factor Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
3
1
Order By: Relevance
“…These findings may support the idea that SSB consumption is pervasive across gender and ethnic groups in South Africa. Contrary to a previous study,21 this study did not find an association between functional disability status and SBB.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings may support the idea that SSB consumption is pervasive across gender and ethnic groups in South Africa. Contrary to a previous study,21 this study did not find an association between functional disability status and SBB.…”
Section: Discussioncontrasting
confidence: 99%
“…Response options were 1=none, 2=every day, 3=1–3 times last week, and 4=4–6 times last week 21. Daily soft drink consumption was calculated from those who said that they would drink a sweetened cold drink every day=1 and none, 1–3 times last week, or 4=4–6 times last week=0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ASD children had unique food preferences ( 39 ), which may have also affected their diet, particularly SSB intake. The previous research reported that individuals with the developmental disabilities were more susceptible to the negative health outcomes associated with SSBs ( 40 ); however, this also depends on the education level of the child's mother. A relatively highly educated mother may decrease their child's SSB intake ( 41 ), therefore, reducing the associated risks, considering the fact that over 50% of the mothers in the ASD group had a bachelor's degree or above, which may explain the lack of differences in SSB intake between ASD and TD children in our study.…”
Section: Discussionmentioning
confidence: 99%